Karakteristik Program dan Kelompok serta Kendala Pelaksanaan Program Simantri di Kabupaten Badung - I PUTU PURNA JAYA; I DEWA PUTU OKA SUARDI; I KETUT BUDI SUSRUSA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Characteristics of Program and Group and Implementation Obstacle Simantri Program in Badung regency Integrated Farming System or Simantri is a breakthrough effort to accelerate the adoption of agricultural technology, Simantri Program development goal is to support integrated diversification of farming to local potentials, to increase income to alleviate poverty, to integrate crop and livestock farming, and to pioneer the development of integrated agriculture in a sustainable manner. The purpose of this research is to investigate the Characteristic of Program and Characteristic of Group, and Constraints of Simantri Program Implementation in the Badung Regency.. The results showed that the Characteristics of Simantri Program is quite good with average achievement score of 3.8, Characteristics of Simantri group is good with average achievement score of 4.1, constraints faced in the characteristics of the program i.e. optimal cattle maintenance management, cattle maintenance, inadequate cage quality and many are not functioningproperly, cow urine channel and bio-urine processing tools are easily damaged, bio-gas was also easily damaged, and the location of Simantri makes the gas bio channel unable to reach the houses of the Simantri's group, group members rarely processed manure because of their other activities, members were reluctant to maintain and care for planted demonstration plots.